Neural correlates of self-focused attention in social anxiety - Böhme, Stephanie; Miltner, Wolfgang H. R.; Straube, Thomas (Social Cognitive and Affective Neuroscience, 2014)
Socially anxious individuals tend to shift their attention away from external socially threatening cues and instead become highly self-focused. Such heightened self-focused attention has been suggested to be involved in the development and maintenance of social anxiety disorder. This study used functional magnetic resonance imaging to investigate the neural correlates of self-focused attention in 16 high socially anxious (HSA) and 16 low socially anxious (LSA) individuals. Participants were instructed to focus their attention either inwardly or outwardly during a simulated social situation. Results indicate hyperactivation of medial prefrontal cortex (mPFC), temporo-parietal junction (TPJ) and temporal pole during inward vs outward attention in HSA compared with LSA participants. Furthermore, activation of mPFC, right anterior insula, TPJ and posterior cingulate cortex was positively correlated with the trait of self-focused attention in HSA subjects. Results highlight the prominent role of the mPFC and other cortical structures in abnormal self-focused attention in social anxiety. Finally, findings for the insula suggest increased processing of bodily states that is related to the amount of habitual self-focused attention in social anxiety.
Created from Fastlane, Scopus look-up
Keywords: fMRI; Insula; mPFC; Self-focused attention; Social anxiety